Framework for digitalized proactive supply chain risk management - Katharina Diedrich (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
In order to initiate proactive measures and to prevent the actual occurrence of risk events a digitalized and proactive supply chain risk management is needed.Existing approaches for digitalized and proactive SCRM are investigated by a systematic literature review and completed by a requirements engineering. Furthermore frameworks for SCRM are reviewed and the fulfillment of the requirements is checked. These results are applied to develop a digitalized and proactive SCRM framework.The findings in this paper are a profile of requirements and a framework, which enables a proactive management of forthcoming risks. Therefore an application of risk prediction and quantitative risk assessment in context of digitalized SCRM is used. The developed framework includes an adapted proactive SCRM process containing digitalized SCRM phases and digitalized SCRM methods, inter alia early knowledge and early assessment
urn:nbn:de:gbv:830-88217547; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; digitalized proactive SCRM; risk information integration; risk prediction; risk assessment